Land for mission and mission for land: A missiological reflection of the Kranspoort Mission Station in Soutpansberg within the Vhembe district of the Limpopo Province - Kgatla, Selaelo T. (University of Pretoria, 2016)
Dissertation (MA)--University of Pretoria, 2016.